Genome-Wide Analysis of TIR-NBS-LRR Gene Family in Potato Identified StTNLC7G2 Inducing Reactive Oxygen Species in Presence of Alternaria solani - Dubey, Namo; Chaudhary, Anjali; Singh, Kunal (Frontiers in Genetics, 2022)
Resistance gene analogs (RGAs) comprising NBS-LRR gene family members are considered prominent candidates in the development of disease-resistant genotypes. NBS-LRR gene family comprised a very large number of genes; therefore, members of one subfamily TIR-NBS-LRR (TNL) are identified in the present study from Solanum tuberosum genome, followed by their bioinformatics characterization. The study identified a total of 44 genes encoding 60 TNL transcripts with two prominent clusters at chromosome 1 and chromosome 11. Expression analysis of 14 TNL genes after Alternaria solani infection at 1, 2, 3, 5, and 7 days post inoculation in two disease-tolerant varieties, Kufri Jyoti and Kufri Pukhraj, and one relatively susceptible variety, Kufri Chandramukhi, showed differential expression of many genes including a high expression (>15-fold) of StTNLC6G2T1 and StTNLC11G9T1. Functional characterization of one such gene, StTNLC7G2, reveals involvement in the generation of reactive oxygen species under A. solani attack, implicating its putative role in plant defense via hypersensitive response.